2021
DOI: 10.15421/112114
|View full text |Cite
|
Sign up to set email alerts
|

The total content of macronutrients and heavy metals in the soil on devastated lands at Kryvyi Rih Iron Mining & Metallurgical District (Ukraine)

Abstract: he relevance of the research is due to the need to develop technologies for phytoremediation of the devastated lands in the mining and metallurgical regions of Ukraine and the world. In this regard, the creation of tree plantations adapted to the ecological conditions of such territories is considered by many experts as the most promising option for innovative technologies. However, the development of artificial woodlands requires knowledge of the pedogeochemical characteristics of devasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…Data about heavy metals contents in this area were already partially presented in our previous publications (Savosko et al, 2021) Mean concentration of metals in the area from highest to lowest was recorded in the following pattern: Fe > Mn > As > Cu > Zn > Cr > Co > Pb > Sn > > Mo > Cd. This model was different from the one obtained at the control site (with the exception of Fe, Mn, Sn, Mo and Cd).…”
Section: Heavy Metals Concentrations In Initial Soil Of Devastated Landsmentioning
confidence: 77%
See 2 more Smart Citations
“…Data about heavy metals contents in this area were already partially presented in our previous publications (Savosko et al, 2021) Mean concentration of metals in the area from highest to lowest was recorded in the following pattern: Fe > Mn > As > Cu > Zn > Cr > Co > Pb > Sn > > Mo > Cd. This model was different from the one obtained at the control site (with the exception of Fe, Mn, Sn, Mo and Cd).…”
Section: Heavy Metals Concentrations In Initial Soil Of Devastated Landsmentioning
confidence: 77%
“…Data about heavy metals contents control sites of Kryvyi Rih District were already partially presented in our previous publications (Savosko et al, 2021). The local background concentrations of these elements and the representative descriptive statistics are summarized in Table 2.…”
Section: Natural Background Concentrations Of Heavy Metals In Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have revealed that in terrestrial ecosystems soil is the main store of many environmental contaminants such as trace metals (Gryshko et al 2012, Baghaie and Aghili 2019, Kasiuliene et al 2019, Savosko et al 2021a. Heavy metals (HMs) are non-degradable and persistent components, therefore their presence in soil is very stable and very long-lasting (Demkova et al 2017, Savosko et al 2021b, Stofejova et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of HMs in soils have presented many problems for agricultural industry, food chains, biosphere functions and human health (Gryshko et al 2012, Savosko 2016, Baghaie and Aghili 2019, Wang et al 2020. The HMs in the soil are derived from the parent material and various anthropogenic sources, such as agriculture, urbanization and industrialization including mining (Demkova et al 2017, Yi and Cheng 2019, Wang et al 2020, Savosko et al 2021a.…”
Section: Introductionmentioning
confidence: 99%